P21-activated kinase regulates oxygen-dependent migration of vascular endothelial cells in monolayers. Issue 1 (1st January 2021) - Hirose, Satomi; Tabata, Yugo; Sone, Kazuki; Takahashi, Naoyuki; Yoshino, Daisuke; Funamoto, Kenichi
ABSTRACT: The collective migration of vascular endothelial cells plays important roles in homeostasis and angiogenesis. Oxygen tension in vivo is a key factor affecting the cellular dynamics. We previously reported hypoxic conditions promote the internalization of vascular endothelial (VE)-cadherin and increase the collective migration of vascular endothelial cells. However, the mechanism through which cells regulate collective migration as affected by oxygen tension is not fully understood. Here, we investigated oxygen-dependent collective migration, focusing on intracellular protein p21-activated kinase (PAK) and hypoxia-inducing factor (HIF)-1α. The results indicate that the oxygen-dependent variation of the migration speed of vascular endothelial cells is mediated by the regulation of VE-cadherin through the PAK pathway, as well as other mechanisms via HIF-1α, especially under extreme hypoxic conditions.